Investigating the Effect of Knowledge-Based Indicators on the Efficiency of Agricultural Production Cooperative Companies in Mazandaran Province - somayeh shirzadi laskookalayeh; Parvin Ghaderinejad (تعاون و کشاورزی)
One of the basic axes of development is knowledge-oriented production activities. The high vulnerability of the agricultural sector, on one hand, and the high importance of this sector in providing food security, on the other hand, have caused agriculture in Iran to take a step towards becoming knowledge-based. In this regard, production cooperatives by consolidating small lands and applying correct management through the use of scientific methods and Tendency towards using new technology in production can provide the basis for increasing the productivity of this sector. Therefore, the current research was conducted with the aim of investigating the state of using new science and modern equipment in the agricultural sector and their effect on the efficiency of cooperatives.Methodology/approach: In this study, the types of efficiency of 29 rural production cooperative companies in Mazandaran province are measured using Data Envelopment Analysis method. For this purpose, DEAP2.1 software is used.Findings and conclusions: The results show that only 17.24% of the investigated cooperatives are efficient in terms of technical and scale, 31.03% in terms of management, 6.90% in terms of allocation and economy. Also, there is a big gap (82.10%) between the technical efficiency of knowledge- based cooperatives and resource- based cooperatives, so it is suggested that the managers of cooperatives in this province should set the cooperatives of Amol as their model and trying in benefiting from new science and technology in production.